Posttranscriptional Gene Regulatory Networks in Chronic Airway Inflammatory Diseases: In silico Mapping of RNA-Binding Protein Expression in Airway Epithelium - Ricciardi, Luca; Giurato, Giorgio; Memoli, Domenico; Pietrafesa, Mariagrazia; Dal Col, Jessica; Salvato, Ilaria; Nigro, Annunziata; Vatrella, Alessandro; Caramori, Gaetano; Casolaro, Vincenzo; Stellato, Cristiana (Frontiers in Immunology, 2020)
Posttranscriptional gene regulation (PTGR) contributes to inflammation through alterations in messenger RNA (mRNA) turnover and translation rates. RNA-binding proteins (RBPs) coordinate these processes but their role in lung inflammatory diseases is ill-defined. We evaluated the expression of a curated list of mRNA-binding RBPs (mRBPs) in selected Gene Expression Omnibus (GEO) transcriptomic databases of airway epithelium isolated from chronic obstructive pulmonary disease (COPD), severe asthma (SA) and control subjects, hypothesizing that global changes in mRBPs expression could point to their pathogenetic roles and identify novel disease-related regulatory networks. A published list of 692 mRBPs [Nat Rev Genet 2014] was searched in GEO datasets from bronchial brushings of stable COPD patients (C), smokers (S), non-smokers (NS) controls with normal lung function (n=6/12/12) (GEO ID: GSE5058) and of (SA) and healthy control (HC) (n=6/12) (GSE63142). Fluorescence intensity data were normalized on the medians for fold change (FC) comparisons. FCs were set at ≥ |1.5| with false discovery rate (FDR) of ≤ 0.05. Correlation maps and heatmaps were generated using tMEV tools. DNA sequence motifs were searched using PScan-ChIP. Gene Ontology (GO) was performed with Ingenuity Pathway Analysis (IPA). Significant mRBP expression changes were detected for S/NS, COPD/NS and COPD/S (n= 41, 391, 382, respectively). Of those, 32% of genes changed by FC ≥ |1.5| in S/NS but more than 60% in COPD/NS and COPD/S (n=13, 267, 257, respectively). Genes were predominantly downregulated in COPD/NS (n=194, 73%) and COPD/S (n=202, 79%), less so in S/NS (n=4, 31%). Unsupervised cluster analysis identified in 4/12 S the same mRBP pattern seen in C, postulating subclinical COPD. DNA motifs enrichment for transcriptional regulation was found for downregulated RBPs.Correlation analysis identified five clusters of co-expressed mRBPs. GO analysis revealed significant enrichments in canonical pathways both specific and shared among comparisons. Unexpectedly, no significant mRBPs modulation was found in SA compared to controls. Airway epithelial mRBPs profiling reveals a COPD-specific global downregulation of RBPs shared by a subset of control smokers, functional cooperation by coexpressed RBPs and significant impact on relevant pathogenetic pathways in COPD. Elucidation of PTGR in COPD could identify disease biomarkers or pathways for therapeutic targeting.